"Forging Peace in 2025-2030: The Role of Canada and South Korea as Middle Powers in Leading Global Conflict Resolution" (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
This article offers a fresh and compelling look at how Canada and South Korea—two influential middle powers—can reshape the global approach to peace and security. It traces South Korea’s robust journey from military rule to democratic resilience and its ongoing efforts to engage North Korea in peace and denuclearization talks. In parallel, Canada’s experience with a nuclear-armed neighbor underscores the shared challenges both nations face. Rather than relying on outdated military alliances and Cold War mindsets, the article calls for bold new coalitions and innovative security alliances that champion diplomacy, peacebuilding, and multilateral cooperation. It argues that Canada and South Korea are uniquely positioned to lead a global shift away from militarization—toward dialogue, conflict prevention, and peace education. With the rise of emerging technologies like drones and AI-driven warfare, the need for forward-thinking diplomatic strategies is more urgent than ever. The article ends with a powerful vision: a reimagined global security order led by middle powers that dare to challenge the status quo and light the path toward a more peaceful, nuclear-free world.
Keywords: Canada; South Korea; nuclear proliferation; peacebuilding; democracy